Analisis Rekrutment dan Penempatan Kerja pada Kinerja Karyawan Perusahaan Trans Berjaya - Sri Mulyeni; Santi Santi; Lien Nurliah; Imas Siti Masitoh; Hanifah Sukmana; Sobarna Kartamihardja (CiDEA Journal, 2023)
The research explains the relationship between employee recruitment and work placement on employee performance at CV Trans Berjaya, the research sample used is a saturated sample because population under 100. The research instrument used a questionnaire, tested data through partial and simultaneous tests, multiple regression test using SPSS 25 software. Partial test results revealed that variabel X1 recruitment affected employee performance by 0,722 or 72,2% and variable X2 work placement influenced performance employees by 0,631 0r 63,1%. And the simultaneous test of recruitment and work placement variables on employee performance has an impact of 0,731 or 73,1%. Thus, the performance of Trans Berjaya employees is influenced by recruitment and job placement. Variables X1 and X2 have a positive and significant effect variable Y.